Clinical, Hematological Profile, and Birth Outcomes of Neonates of Mothers with Hypertension Complicating Pregnancy in India—An Observational Study - Cherukuri Nirmala; Manohar P. Kankati; Paramesh Pandala; Kotha Rakesh (International Journal of Medicine and Health Development)
Background: Hypertensive disorders during pregnancy pose significant risks to both maternal and fetal health. Maternal hypertension has the potential to affect all the systems of the newborn, including the hematological system. Objective: To identify deviations in hematological parameters and birth outcomes in babies born to mothers with hypertensive disorders of pregnancy. Materials and Methods: An observational case–control study was carried out on neonates born to hypertensive mothers in Niloufer Hospital, Hyderabad, India. The study was done over 18-month period from January 2021 to August 2022. The cases comprised babies born to mothers with hypertensive disorders of pregnancy, while controls were babies of normotensive mothers. The hematological parameters measured included hemoglobin (Hb) level, platelet count, mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), mean corpuscular volume (MCV), and white blood cell (WBC) count. Results: The neonates of hypertensive mothers had significantly lower levels of Hb (P = 0.02), WBC (P = 0.001), MCH (P = 0.01), and MCHC (P = 0.004). Also, platelet counts were significantly lower among neonates of hypertensive mothers (P = 0.001). They also had significantly lower birth weights than the controls (P = 0.01). Conclusion: This study pinpointed substantial changes in the hematological profile and birth outcomes of neonates born to mothers with hypertensive disorder of pregnancy. These findings underscored the importance of considering these alterations when interpreting hematological values in these infants, necessitating early detection and comprehensive healthcare strategies for neonates at high risk in India. Future research should consider the long-term outcomes of these hematological parameters to elevate the understanding and guide interventions.